2003
DOI: 10.1080/0275754031000087074
|View full text |Cite
|
Sign up to set email alerts
|

Water quality in the Red Sea coastal waters (Egypt): Analysis of spatial and temporal variability

Abstract: In order to provide a background picture of the water quality of the Egyptian Red Sea a number of hydrological and chemical parameters have been measured bimonthly in 2000. Few data are available on this area, which is apparently subjected to an increasing human impact due to recreational (swimming and diving), industrial (mainly phosphate shipping and industry) and fishing=harbor activities. The results of the present study indicate that changes in the salinity and pH were not significant with highly oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 2 publications
1
18
1
Order By: Relevance
“…Central Red Sea reefs are characterized by unique environmental conditions of high temperature, salinity, TA, and oligotrophy (Fahmy, 2003;Kleypas et al, 1999;Steiner et al, 2014). On a global scale they support remarkable reef growth, sustaining well-established fringing reefs along most of the coastline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Central Red Sea reefs are characterized by unique environmental conditions of high temperature, salinity, TA, and oligotrophy (Fahmy, 2003;Kleypas et al, 1999;Steiner et al, 2014). On a global scale they support remarkable reef growth, sustaining well-established fringing reefs along most of the coastline.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study also identified PO 3− 4 concentration as an abiotic correlate of reef growth. In the Red Sea, high N : P ratios indicate that P is a limiting micronutrient, e.g., for phytoplankton (Fahmy, 2003). PO 3− is not only essential for pelagic primary producers, but also for reef calcifiers and their photosymbionts, such as the stony corals and their micro-algal Symbiodiniaceae endosymbionts (Ferrier-Pagès et al, 2016;LaJeunesse et al, 2018).…”
Section: Total Alkalinity and Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, P-limitation was suspected in various areas in the global ocean Swift 1982, Smith 1984), and this topic has more recently seen renewed interest (Karl 2000, Wu et al 2000, Moore et al 2008. Phosphorus has been reported to occur at growth-limiting levels for phytoplankton in the subtropical Atlantic Swift 1979, Wu et al 2000), Mediterranean Sea (Berland et al 1972, Thingstad et al 2005, Red Sea (Fahmy 2003), and Gulf of Mexico (Hardison et al 2013). High N:P ratios, elevated alkaline phosphatase (AP) activity, molecular 12 SENJIE LIN ET AL.…”
Section: Oceanmentioning
confidence: 99%
“…P is incorporated into vital biomolecules that play essential roles in cellular structure (phospholipids), the storage and transmission of genetic information (DNA and RNA), energy transduction (adenosine 5 -triphosphate; ATP), metabolic signaling (inositol trisphosphate, (de)phosphorylated proteins and metabolites), as well as stress response and homeostasis (inorganic polyphosphate; poly-P) (Kornberg et al, 1999;Gray and Jakob, 2015). Although marine primary production is principally limited by either nitrogen or iron over most of the global surface ocean (Moore et al, 2013), P can be present at low or limiting concentrations in many marine systems, from the vast oligotrophic gyres (Rivkin and Swift, 1979;Wu et al, 2000;Moore et al, 2008;Moore et al, 2013) to coastal seas (Berland et al, 1972;Fahmy, 2003;Thingstad et al, 2005;Hardison et al, 2013). Rising anthropogenic inputs of nitrogen have also led to an increasing prevalence of P limitation in many ocean environments, especially in near-shore zones (Harrison et al, 1990;Fisher et al, 1992Fisher et al, , 1999Huang et al, 2003;Kemp et al, 2005;Zhang et al, 2007;Xu et al, 2008;Fu et al, 2012;Laurent et al, 2012;Turner and Rabalais, 2013;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%